Id4 knockdown during zebrafish development revealed its functional role in neural stem cell survival - Patlola, Santosh (2010)
Id4 (Inhibitor of DNA binding 4 / Inhibitor of Differentiation 4) is one of the four members of Id protein family that antagonise the function of basic helix-loop-helix (bHLH) transcriptional regulators. In the mouse it has been shown that Id4 plays an important role in the timing of neural stem and progenitor cell differentiation and knockout mice exhibited premature neural stem cell differentiation resulting in significantly smaller brains. To further establish the molecular mechanism underlying Id4 function in neural stem cells during the development of the brain using zebrafish as the model organism. Antisense morpholinos that specifically block translation of the Id4 transcripts were employed to knockdown the expression of Id4 during early zebrafish development. Embryos injected with increasing amounts of Id4 morpholinos exhibited a dose-dependent phenotype at 24 hours post fertilisation (hpf) showing severely damaged and malformed brains with no distinct boundaries. Co-injection of Haemagglutinin (HA)-tagged zebrafish Id4 cDNA (containing the morpholino target sequence) did not rescue the Id4 morphants, but co-injection of HA-tagged mouse Id4 mRNA (not containing the morpholino target sequence) did result in a partial rescue of the phenotype indicating specificity of the knockdown. Western-blot analysis revealed that over expressed HA-tagged Id4 protein was abundant at 8 hpf but levels decreased at 18 hpf and at 24 hpf HA-tagged Id4 protein was undetectable suggesting a rapid turnover of the protein. Nevertheless, injection of high amounts of Id4 cDNA also gave rise to a phenotype with embryos exhibiting malformed head, brain and tail. Preliminary Terminal deoxynucleotidyl Transferase dUTP Nick End Labelling (TUNEL) assays indicated that Id4 knockdown resulted in an increase in apoptosis in the developing nervous system suggesting a role of Id4 in neural stem cell survival.